Memórias, práticas e discursos sobre a leitura - Gurjão, Mônica Vieira de Sousa (2009)
The theme of the reading, in spite of constantly re-visited through inquiries, discussions, seminars, symposium, presents itself still an object of investigation. The importance of these investigations increase while grows the concern on how to form "competent" readers, principally when official rates, just like the spread ones for the IDEB, reveal the low performance of the pupils regarding the reading. This research, allying to this problematic, intends like general objective to contribute to reveal other possibilities to the reading be investigated, enlarging the conception of what is to read and how to read it. For so much, we are based in studies like those of Abreu (1999), Kleiman (1995, 2002), Sousa (2002, 2005, 2008), Manguel (1997), Geraldi (1997), Lajolo (2004), Coracini (2002), between others. We leave from the hypothesis of which to recover histories of reading is to contribute to the reanalysis of inner school reading practice. We analyze speeches on the reading, from data obtained in interviews carried out with three teachers who act in the first phase of the Basic Teaching, in a school of the State Public Net of Education in the city of Campina Grande, and nine pupils of these teachers. We use interviews that were of semi-structured questions, which were mainly about histories and practices of reading so much of these teachers as well as of all the pupils. Initially, we look to identify the methods in which the teachers were taught to read and write and like this fact it is represented in the Brazilian Literature. Subsequently, our intention was directed in their methods of forming readers. For end, we establish a counterpoint between what the teachers and the pupils say about their reading preferences. The analyses of the interviews point to the reading conceptions in which the teachers were taught to read and write and, at the same time, demonstrate differentiated means of practices of reading in the school. The analyses also indicated that there is a superposition of influences, so that the relation between the reading that the teachers say to carry out and the reading practiced in classroom do not seem to be so straight, in other words, what the teachers affirm to read does not reveal an activity that contributes with the pedagogic practice. And for last, we realize that the teachers do not recognize the contribution of the family for the reading formation of their pupils, just as they also do not know their students reading practices.